2017
DOI: 10.1007/s00246-017-1705-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Growth Differentiation Factor-15 is a Potential Biomarker for Pediatric Pulmonary Arterial Hypertension Associated with Congenital Heart Disease

Abstract: We aimed to investigate plasma growth differentiation factor-15 (GDF-15) levels in pediatric pulmonary arterial hypertension secondary to congenital heart disease (PAH-CHD), and assess the association with hemodynamic parameters. Plasma GDF-15 levels were measured in children with PAH-CHD (n = 46) and compared to children with CHD without PAH (n = 39). Normal individuals (n = 30) served as health control group. Plasma GDF-15 levels were significantly elevated in patients with PAH-CHD compared with those with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
7
30
1
Order By: Relevance
“…Our study revealed that GDF-15 levels were significantly higher in CHD patients with severe PH compared to those with mild or moderate PH. This comes in agreement with the results of Li et al who found that plasma GDF-15 levels were closely correlated with disease severity of PH in children with PH-CHD and GDF-15 had a significant positive correlation with both mPAP and PVR, suggesting a pathological role that is directly linked to the increased pressure in pulmonary vasculature [12]. Moreover, Nickel et al revealed that GDF-15 was abundantly found in pulmonary vascular endothelial cells in patients with idiopathic PH suggesting that it had a role in the pathogenesis of PH [8].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study revealed that GDF-15 levels were significantly higher in CHD patients with severe PH compared to those with mild or moderate PH. This comes in agreement with the results of Li et al who found that plasma GDF-15 levels were closely correlated with disease severity of PH in children with PH-CHD and GDF-15 had a significant positive correlation with both mPAP and PVR, suggesting a pathological role that is directly linked to the increased pressure in pulmonary vasculature [12]. Moreover, Nickel et al revealed that GDF-15 was abundantly found in pulmonary vascular endothelial cells in patients with idiopathic PH suggesting that it had a role in the pathogenesis of PH [8].…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed that plasma levels of GDF-15 were significantly higher in PH-CHD patients compared to CHD only patients and control group. This agreed with Li et al who found that GDF-15 levels were higher in children with PH-CHD [12]. PH leads to an increase of pressure overload on the right ventricle with a resultant increase of plasma GDF-15 that found to be increased in conditions characterized by hypoxia or pressure overload [7][8][9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…GDF-15 in elevated concentrations was found in numerous CV diseases, such as LV hypertrophy, stable CAD, myocardial infarction / acute coronary syndrome, acute and chronic HF, asymptomatic atherosclerosis [12,[23][24][25]. Moreover, GDF-15 has positively associated with LV mass, levels of IL-6 and matrix metalloproteinase (MMP)-9 levels [24].…”
Section: Association Between Growth-differentiation Factor-15 and CV mentioning
confidence: 99%
“…In patients with pulmonary arterial hypertension secondary to congenital heart disease (CHD) serum levels of GDF-15 were significantly increased compared with CHD individuals without pulmonary arterial hypertension [25]. Authors reported that elevated plasma levels of GDF-15 positively associated with NYHA functional class, serum uric acid, NT-proBNP, pulmonary artery systolic pressure, mean pulmonary artery pressure, pulmonary blood flow, systemic blood flow and pulmonary vascular resistance, and as well as a lower mixed venous oxygen saturation [25]. It has been determined that the diagnostic value of NT-pro BNP and GDF-15 in turn of pulmonary arterial hypertension was similar.…”
Section: Association Between Growth-differentiation Factor-15 and CV mentioning
confidence: 99%